'A smile stands for health and a bed for illness': Graphic cues in children's drawings. (November 2019) - Bonoti, Fotini; Christidou, Vasilia; Spyrou, Georgia Maria
Objective: The study aimed to investigate whether children use specific types of graphic cues (facial, postural, contextual) in their drawings of healthy and ill persons and whether these cues differ as a function of age. Design: Cross-sectional design. Setting: A public primary school in a medium-sized city in Greece. Method: A total of 200 children in the age group of 5, 7, 9 and 11 years were first asked to define the terms under investigation, and then to draw a healthy and an ill person, as well as a baseline drawing (of a person neither healthy nor ill). Human figure drawings of health and illness were compared with their baseline drawing in an attempt to detect possible alterations in the (1) face, (2) body and (3) overall context of the drawing. Results: From the age of 5 years onwards, children were able to use a combination of graphic cues to convey health and illness in their drawings. Moreover, children in all age groups more often (1) employed facial cues to depict illness and health, (2) used more postural and contextual cues to depict illness than health, (3) introduced a variety of contextual cues in their drawings (e.g. linguistic, nutritional, environmental, physical and medical) and (4) used more types of graphic cues as well as more categories of contextual cues to depict illness than health. Finally, it was found that the drawings of the 5-year-old children involved significantly fewer graphic cues than those of the 7- and 11-year-olds, and significantly less contextual cues than the drawings produced by the 9- and 11-year-olds. Conclusion: Study findings shed light on the way children perceive and represent graphically illness and health and these are discussed in relation to their implications for health education.